2015
DOI: 10.15376/biores.10.2.3154-3168
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Approach for Optimization of Ethanol Production from Fast-growing Trees: Acacia mangium and Acacia hybrid

Abstract: This is the first report of the potential of Acacia fast growing trees in Thailand, A. mangium and the Acacia hybrid (A. mangium x A. auriculiformis), as raw material for ethanol production through a simultaneous saccharification and fermentation process by Saccharomyces cerevisiae TISTR 5339. Alkaline pulping was applied as the pretreatment process. Optimization of ethanol production was studied using response surface methodology based on central composite design. The optimized conditions of 100 g/L solid loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As improvements, we can mention the increase in HHV (19.58 to 20.63 MJ kg -1 ) and the fixed carbon content (14.7 to 19.1%). This result may be related to the chemical composition of A. mangium bark, as demonstrated by Rosdiana et al (2017) and Vega et al (2019), with total extractives content in the order of 17-34%, higher than the extractives content found in the wood of this same specie, between 4-6% (BOONDAENG et al, 2015;VEGA et al, 2019). In its chemical composition, bark differs from wood by the presence of polyphenols and a higher percentage of extractives (ROSDIANA et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…As improvements, we can mention the increase in HHV (19.58 to 20.63 MJ kg -1 ) and the fixed carbon content (14.7 to 19.1%). This result may be related to the chemical composition of A. mangium bark, as demonstrated by Rosdiana et al (2017) and Vega et al (2019), with total extractives content in the order of 17-34%, higher than the extractives content found in the wood of this same specie, between 4-6% (BOONDAENG et al, 2015;VEGA et al, 2019). In its chemical composition, bark differs from wood by the presence of polyphenols and a higher percentage of extractives (ROSDIANA et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…The ethanol concentration was analyzed using gas chromatography (Chromosorb-103, GC4000; GL Sciences; Tokyo, Japan) with an HP5 capillary (30 m × 0.32 mm × 0.25 µm; JW Scientific; Folsom, CA, USA) and FID detector under the following conditions: split flow, 50 mL/min; air flow, 250 mL/min; N2 carrier flow, 30 mL/min; column temperature, 185 °C; injector temperature, 250 °C; detector temperature, 250 °C. n-Propanol was used as the internal standard for comparison [ 42 ]. All measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from the cassava stem, other lignocellulose residues were also reported ( Table 3). The cellulose content from the cassava stem was compared to other reported cellulose content such as 44% for Acacia mangium and 42% for Acacia hybrid (Boondaeng et al, 2015), 26-43% for bamboo (Sánchez, 2009), 42-45% for corn cob (Kuhad and Singh, 1993;Prasad et al, 2007;Liu et al, 2010), 20-25% for hardwood (McKendry, 2002), 43% for the empty fruit bunch of oil palm (Garcia-Nunez et al, 2016), 28-36% for rice straw (Chen et al, 2008;Saini et al, 2015), 27-30% for softwood (McKendry, 2002), 42-48% for sugarcane bagasse (Kuhad and Singh, 1993;Rocha et al, 2015;Saini et al, 2015) and 5-34% for switch grass (Butkute et al, 2013;Saini et al, 2015). These figures indicated that cassava stem has a high potential to be used as a feedstock in bioconversion processes for ethanol fermentation, especially as it can be obtained in large quantities from local growers.…”
Section: Chemical Composition Of Cassava Stem Woodmentioning
confidence: 99%
“…In the past decade, energy supply has been a primary concern as the global supply of petroleum is depleting (Owusu and Asumadu-Sarkodie, 2016). First generation biofuels that are made from starch, sugar and vegetable oil from crops, have raised some concerns regarding their economic benefits and the inability to produce adequate biofuels without threatening food supply (Boondaeng et al, 2015). As such, the search for new sources of biofuels has captivated global interest with lignocellulosic biomass-the most abundant feedstocks for a second generation biofuel -being of particular interest due to its low cost, as it can serve as an alternative to various raw materials such as agro-wastes, forestry wastes and pulp wastes (Saha, 2004;Talebnia et al, 2010;Chen, 2011;Singh and Bishnoi, 2012).…”
Section: Introductionmentioning
confidence: 99%